Resolving molecular frontier orbitals in molecular junctions with kHz resolution - Isshiki, Yuji; Montes, Enrique; Nishino, Tomoaki; Vázquez, Héctor; Fujii, Shintaro (Chemical science, 2024)
Designing and building single-molecule circuits with tailored functionalities requires a detailed knowledge of the junction electronic structure. The energy of frontier molecular orbitals and their electronic coupling with the electrodes play a key role in determining the conductance of nanoscale molecular circuits. Here, we developed a method for measuring the current-voltage (I-V) characteristics of single-molecule junctions with a time resolution that is two orders of magnitude higher than previously achieved. These I-V measurements with high temporal resolution, together with atomistic simulations, enabled us to characterize in detail the frontier molecular states and their evolution in sub-angstrom stretching of the junction. For a series of molecules, changes in the electronic structure were resolved as well as their fluctuations prior to junction breakdown. This study describes a new methodology to determine the key frontier MO parameters at single-molecule junctions and demonstrates how these can be mechanically tuned at the single-molecule level.